2016
DOI: 10.3390/ijms17081257
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic Acid Induces Oxidative DNA Damage and Apoptosis, and Enhances the Chemosensitivity of Cancer Cells

Abstract: The human diet contains low amounts of ω-3 polyunsaturated fatty acids (PUFAs) and high amounts of ω-6 PUFAs, which has been reported to contribute to the incidence of cancer. Epidemiological studies have shown that a high consumption of fish oil or ω-3 PUFAs reduced the risk of colon, pancreatic, and endometrial cancers. The ω-3 PUFA, docosahexaenoic acid (DHA), shows anticancer activity by inducing apoptosis of some human cancer cells without toxicity against normal cells. DHA induces oxidative stress and ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 69 publications
4
35
0
Order By: Relevance
“…We recently summarized that oxidized DHA leads to DNA adduct formation. Oxidative DNA damage triggers cell cycle arrest and apoptosis by p53-dependent and p53-independent pathways in cancer cells 30. Zhang et al31 reported that DHA and EPA inhibits proliferation and induce apoptosis of human SW 1990 pancreatic cancer cells by down-regulating cyclin E expression.…”
Section: Effect Of Docosahexaenoic Acid On Pancreatic Carcinogenesismentioning
confidence: 99%
“…We recently summarized that oxidized DHA leads to DNA adduct formation. Oxidative DNA damage triggers cell cycle arrest and apoptosis by p53-dependent and p53-independent pathways in cancer cells 30. Zhang et al31 reported that DHA and EPA inhibits proliferation and induce apoptosis of human SW 1990 pancreatic cancer cells by down-regulating cyclin E expression.…”
Section: Effect Of Docosahexaenoic Acid On Pancreatic Carcinogenesismentioning
confidence: 99%
“…Several preclinical (in vitro and in vivo) studies and some human experimental studies have demonstrated the ability of ω-3 PUFA to decrease cancer cell proliferation, to promote cancer cell death and to inhibit neoangiogenesis in cancer [ 47 , 48 , 49 ]. Interestingly, these anticancer effects are induced by ω-3 PUFA only in cancer cells and not in normal cells [ 50 ].…”
Section: ω-3 Pufa and Cancermentioning
confidence: 99%
“…Overall, the suppression of cell survival pathways and induction of cell death are among the most important mechanisms to explain the chemosensitizing effects of these fatty acids in a variety of cancers [ 13 ]. The suppression of cancer cell stemness has also been recently reported [ 68 ], and multiple results have suggested that oxidative stress-induced cytotoxicity plays a central role [ 13 , 48 , 68 ], particularly if the drugs used in combination with ω-3 PUFA were themselves inducers of oxidative stress (such as ATC, or disulfiram) [ 68 ].…”
Section: Potential Adjuvant Role Of ω-3 Pufa In Combination With Amentioning
confidence: 99%
“…Additionally, NAC pretreatment reduced FOXO3-induced early ROS peak, which was shown to be essential for the secondary apoptosis-inducing ROS peak[ 47 ]. Furthermore, docosahexaenoic Acid (DHA) was shown to trigger ROS, p53 activation and cell death in multiple cancer cell lines including colon cancer cells, which could be prevented by pretreatment with antioxidants including NAC[ 48 ]. To explore the involvement of ROS production in DNA damage-induced cell death in HCT-116 wt and p53 -/- cells, we pretreated the cells with NAC or TIRON followed by treatment with cisplatin or UV and we measured the cell viability by CellTiterGlo cell viability assay.…”
Section: Resultsmentioning
confidence: 99%